2003
DOI: 10.1002/etc.5620220417
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for laboratory studies on volatilization: Extension of applicability of the photovolatility chamber

Abstract: Volatilization from soil and plant surfaces after application is an important source of pesticide residues to the atmosphere. The laboratory photovolatility chamber allows the simultaneous measurement of volatilization and photodegradation of 14C-labeled pesticides under controlled climatic conditions. Both continuous air sampling, which quantifies volatile organic compounds and 14CO2 separately, and the detection of surface-located residues allow for a mass balance of radioactivity. The setup of the photovola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…During the following days volatilization rates decreased and finally reached extremely low constant daily rates. These results correspond to the volatilization kinetics observed in an interlaboratory comparison of volatilization assessment methods and were also measured in a laboratory study under moist conditions using the same soil (Walter, 1998; Wolters et al, 2003). However, the environmental conditions fail to explain the observed volatilization kinetics; for example, a clear correlation between volatilization rates and soil moisture was not measured (Fig.…”
Section: Resultssupporting
confidence: 79%
“…During the following days volatilization rates decreased and finally reached extremely low constant daily rates. These results correspond to the volatilization kinetics observed in an interlaboratory comparison of volatilization assessment methods and were also measured in a laboratory study under moist conditions using the same soil (Walter, 1998; Wolters et al, 2003). However, the environmental conditions fail to explain the observed volatilization kinetics; for example, a clear correlation between volatilization rates and soil moisture was not measured (Fig.…”
Section: Resultssupporting
confidence: 79%
“…A large number of studies have shown that sorption in air-dry soils does not only occur in soil organic matter but also on mineral surfaces (e.g., refs 3-10). The strong moisture effect that has been found in field studies and wind-tunnel experiments on the volatilization of pesticides (1,(11)(12)(13)(14) has been attributed to the effect of water on adsorption to mineral surfaces as early as 1969 (15). It is therefore remarkable to find that, to date, approaches for modeling sorption of organic compounds in soils have completely ignored the sorption capacity of mineral surfaces and have concentrated on sorption to soil organic matter only.…”
Section: Introductionmentioning
confidence: 99%
“…The overall aim of this study was the quantification of the effect of direct and indirect photodegradation on surface-located antibiotics after application to soil dust and glass surfaces under laboratory conditions. A well-established experimental facility developed for the simultaneous measurement of photodegradation and volatilization of xenobiotics was used to allow for defined and reproducible conditions ( , ). Sulfadiazine, a sulfonamide widely used as a veterinary antibiotic within the European Union (), was chosen for the studies.…”
Section: Introductionmentioning
confidence: 99%